Development of an Off-Axis Digital Holographic Microscope for Large Scale Measurement in Fluid Mechanics - Tamrin, K. F.; Rahmatullah, B.; Samuri, S. M. (Springer, Cham, 2015)
Holographic particle image velocimetry is a promising technique to probe and characterize complex flow dynamics since it is a truly three-dimensional (3D) three-component measurement technique. The technique simply records the coherent light scattered by small seeding particles that are assumed to faithfully follow the flow and uses it to reconstruct the event afterward. Reconstruction of the event is usually performed using a digital video microscope mounted on a 3D translation stage. The microscope records the intensity only which consequently results in loss of phase information. The objective of this paper is to develop and apply digital holographic microscopy with the aim to recover the phase information. Digital holographic microscopy has immense potentials in microscale solid and fluid measurements as it offers the possibility of digital wavefront processing by manipulating amplitude and phase of the recorded holograms. In this paper, we have developed an off-axis digital holographic microscope to capture both amplitude and phase of the reconstructed object simultaneously. This inherently solves twin image problem in the recorded digital holograms. The microscope was integrated into the reconstruction system and was successfully used to digitize holographic images of 10 μm polystyrene spheres and 1 μm olive oil droplets. The spatial resolution of the system is 0.63 μm, and the field of view is 1250 × 625 μm2. A 3D holographic reconstruction using a k-space analysis (wave-vector) of the optical field is applied to numerically refocus the images. Another potential application includes digital wavefront processing to compensate for aberration in the images.